HAK DAN KEWAJIBAN INVESTOR ASING DITINJAU DARI UNDANG-UNDANG NOMOR 25 TAHUN 2007 TENTANG PENANAMAN MODAL - Febby Sara Sitradewi, Kadek; Dharma Kusuma, Anak Agung Gede Agung (Kertha Semaya : Journal Ilmu Hukum, 2014)
According to Act Number 25 of 2007 about investment, obvious as a form of business activities by way of capital investment by both domestic investors and foreign investors in the territory of the Republic of Indonesia, which foreign capital owned by the state, individual foreign nationals, either a foreign legal entity or Indonesian legal entity which partially or wholly owned by foreign parties in the form of assets that have economic value. Possibility of disagreement or dispute between the parties should not be ignored. The method used is a normative legal research methods, in particular by examining the principles of law, legal systematics, and the synchronization level of legal. The goal was to determine the rights and obligations of foreign investors by Act No. 25 of 2007. One of the right and obligations of foreign investors by Act No. 25 of 2007 is open information about the field of business being operated and apply the principles of good corporate governance.
Keywords: Right,Obligation, Foreign Investors